2017
DOI: 10.1055/s-0043-107785
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise During Pregnancy – How Active Are Pregnant Women in Germany and How Well Informed?

Abstract: ABSTR AC TIntroduction There is sufficient evidence showing the positive effects of physical exercise on various aspects of pregnancy. This study evaluates knowledge and status of physical exercise among pregnant women. MethodsThe standardised paper-pencil questionnaire "Pregnancy Physical Activity Questionnaire" (PPAQ) as well as general demographic questions were used to assess the exercise behaviour of study participants. 83 questionnaires completed by women presenting to the Kiel University Hospital for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 36 publications
(37 reference statements)
2
27
0
5
Order By: Relevance
“…In the current study it was found that household and caregiving activities were the most common types of PA among Polish pregnant women, which is consistent with the findings of Chandonnet et al, in their study of French women [34], and Schmidt et al, in a group of German women [35]. Nevertheless, these women more often engaged in sports activities.…”
Section: Characteristics Of the Study Population Are Presented Insupporting
confidence: 92%
“…In the current study it was found that household and caregiving activities were the most common types of PA among Polish pregnant women, which is consistent with the findings of Chandonnet et al, in their study of French women [34], and Schmidt et al, in a group of German women [35]. Nevertheless, these women more often engaged in sports activities.…”
Section: Characteristics Of the Study Population Are Presented Insupporting
confidence: 92%
“…Overall, the low proportion (35.8%) of pregnant women who reported receiving PA counseling throughout pregnancy is alarming. We found no longitudinal studies to date assessing PA counseling received throughout pregnancy, but our result is low compared to the cross-sectional studies in the literature [11,12]. This observation adds to the concerns about the rise in maternal obesity and the related complications [13].…”
Section: Discussionmentioning
confidence: 59%
“…Scientific evidence has proven the risks of physical activity during pregnancy are rare [1]. However, the rate of prenatal activity is reportedly low, both in developed [10][11][12] and developing countries [13][14][15][16][17][18]. Put differently, few women meet the authoritative guidelines of physical activity during pregnancy, perhaps, due to varying factors.…”
Section: Introductionmentioning
confidence: 99%